1978
DOI: 10.1042/bj1720123
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyl transfer from nucleotide sugars to C85- and C55-polyprenyl and retinyl phosphates by microsomal subfractions and Golgi membranes of rat liver

Abstract: The capacity of isolated membrane fractions to catalyse transfer of sugars from sugar nucleotides to alpha-saturated and non-saturated forms of phosphorylated C85 and C55 polyprenols and retinyl phosphate was examined. The amount of endogenous lipid acceptor present for various sugars was also measured. It appears that the types and amounts of polyprenyl phosphates present in rough- and smooth-microsomal fractions and Golgi membranes are different and the individual polyprenyl phosphates exhibit specificity as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

1978
1978
1988
1988

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 13 publications
(6 reference statements)
4
15
1
Order By: Relevance
“…Information about the importance of polyisoprenoid structure to the glycosylation process is also available (Table 5). a-Saturation of dolichyl phosphate is a requirement for its reaction with activated nucleotidesugars [35][36][37]. The isoprene length of polyisoprenes occurring in animal cells has no influence on the construction of the sugar chain: all individual dolichols react equally well with the different activated monosaccharides [37][38][39].…”
Section: Functions Of Dolichyl Phosphatementioning
confidence: 99%
“…Information about the importance of polyisoprenoid structure to the glycosylation process is also available (Table 5). a-Saturation of dolichyl phosphate is a requirement for its reaction with activated nucleotidesugars [35][36][37]. The isoprene length of polyisoprenes occurring in animal cells has no influence on the construction of the sugar chain: all individual dolichols react equally well with the different activated monosaccharides [37][38][39].…”
Section: Functions Of Dolichyl Phosphatementioning
confidence: 99%
“…In the present studies, the activity in smooth membranes was about equal to that in Golgi apparatus, a fraction found to have very low activity by Bergman et al (1978). The only substantial differences between the conditions used by Bergman et al (1978) and those used by us that could account for the differences in the results obtained are: (1) their use of microsomal phospholipid in the incubation mixture; and (2) their use of dimethyl sulphoxide as solvent where we used the detergent Triton X-100. We conducted tests with whole-microsomal-membrane fractions and found that the omission of phospholipid had no effect on mannosyl retinyl phosphate formation.…”
Section: Discussionmentioning
confidence: 72%
“…Other reasons for believing our results to be more reliable than those of Bergman et al (1978) are: (1) we quantitatively standardized our isolation procedure for mannosyl retinyl phosphate by using doubly labelled mannosyl retinyl phosphate to test reproducibility; (2) we evaluated our results statistically (for both reproducibility of the assay and distribution of enzyme activity) and reported standard deviations, whereas Bergman et al (1978) Arnold et al (1976) reported that plasma membrane of chick embryo liver was active in mannosyl retinyl phosphate formation. In the present work this fraction had negligible mannosyl retinyl phosphate-forming activity.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Dolichol phosphates appear to have a broad and uneven distribution in intracellular membranes [5]. In addition the number of isoprene residues influences the interaction of this lipid with specific glycosyl transferases [6]. These findings indicate that dolichol phosphates may play a regulatory role in glycoprotein synthesis.…”
Section: Introductionmentioning
confidence: 81%